Environmental impact lifecycle assessment of green sand moulding in foundries - Karadimas, Georgios; Pagone, Emanuele; Birch, Tim (Springer, 2025)
The metal casting industry faces significant challenges in reducing its environmental impact. This paper presents a study aimed at evaluating and minimizing the environmental effects of green sand moulding processes. The project uses advanced Life Cycle Assessment (LCA) methodologies, specifically the ReCiPe method, to analyse the entire lifecycle of moulding sand, from extraction to disposal. The study measures emissions during the metal pouring process and identifies key contributors to greenhouse gas emissions. By incorporating sustainable binder technologies and optimizing sand reclamation processes, the project suggests practical strategies for reducing the carbon footprint of foundries. The outcomes include a detailed lifecycle inventory report, an impact assessment highlighting critical areas for intervention, and a practical guide for implementing emission reduction strategies. This research supports global net zero targets and offers a model for sustainable practices in the foundry industry. The findings provide essential insights and feasible strategies for foundries to achieve substantial environmental impact reductions, contributing to a more sustainable future in metal casting. This comprehensive approach ensures that the proposed solutions are both effective and scalable, aligning with broader environmental sustainability goals.
Keywords: 33 Built Environment and Design; 3302 Building; Generic health relevance; 12 Responsible Consumption and Production